Ritual, Identitas, dan Islamisasi Budaya: Parno Pelepasan Haji sebagai Refleksi Lokalitas Islami Kerinci - Auliana Nur Putri; Sustianingsih, Ira Miyarni; Ravico; Yati, Risa Marta; Siregar, Anggi Desviana (CHRONOLOGIA, 2026)
This article examines the contribution of Islam in the culture of the case study of the Hajj parno in Koto Majidin Village. This research explores how Islamic teachings are integrated with local customs in the Hajj ceremony, as well as their impact on the social and cultural life of the local community. The Islamic community in the Koto Majidin traditional area recognizes several important roles such as Depati, Menti Agung, Pati, Rio, and Tumengun. The customs and characteristics of Islam in the village of Koto Majidin are very closely related. The linguistic expressions used in traditional ceremonies are called parno. The method used is a qualitative method in an anthropological approach which includes observation, interviews. The results of this study are seen from the Parno Tradition of the Hajj Discharge Custom in Koto Majidin Village as documentation and information for the Koto Majidin community that preservation is needed. Parno Adat Hajj Release, which is made by traditional leaders and previous people, holds a deep meaning of gratitude and respect for tradition. Islam's contribution to this culture includes aspects of custom, thanksgiving and prayer, togetherness, and ties of brotherhood.